Synthesis of a ‘Propeller-Like’ Oligoheteroaryl with Alternating Pyridine and Oxazole Motifs - Georgiades, Savvas N.; Rizeq, Natalia (Synlett, 2015)
The molecular architecture of oligomeric pyridyl-oxazole compounds is key to determining their mode of interaction with G-quadruplex DNA structures, which is a family of prominent anticancer biomolecular targets. We report herein an efficient synthetic route that begins with chelidamic acid and affords, in just seven steps, an unusual ‘propeller-like’ pyridyl-oxazole architecture with alternating pyridine and oxazole rings, that has not been yet validated as a G-quadruplex binder. The synthesis employs Van Leusen chemistry for the construction of oxazole rings from aldehydes, and two Pd(II)/Cu(I)-mediated cross-coupling reactions involving C–H activation of oxazoles for the formation of C–C bonds between bromopyridine intermediates and oxazole fragments. This modular synthesis was designed to be amenable to the construction of analogues.
Keywords: anticancer; oligoheteroaryl; propeller architecture; C-H activation; G-quadruplex